2023
DOI: 10.1021/acsnano.2c09964
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals the Growth Promotion Mechanism of Enteropathogenic Escherichia coli Induced by Black Phosphorus Nanosheets

Abstract: With the extensive production and application of black phosphorus (BP) nanosheets, release to the environment is inevitable, which raises concerns about the fate and effects of this two-dimensional (2D) material on sensitive receptors such as environmental microbes. Although the bacterial toxicity of BP nanosheets has been demonstrated, whether the biological response differs in pathogenic and nonpathogenic strains of a microorganism is unknown. Here, enteropathogenic Escherichia coli (EPEC) and nonpathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…21 Although BP nanosheets have also been extensively studied for their antibacterial effects, most studies have only utilized the CFU method to evaluate their antibacterial activity. 9, 10 In our previous studies, we noticed a significant discrepancy between the results obtained from the growth curve and CFU methods, 22,23 indicating that BP nanosheets may induce bacteria to enter the VBNC state. This speculation is supported by similar findings reported by Naskar et al 11 However, the underlying mechanisms of this response to BP nanosheets and the induction of the VBNC state by nanomaterials have not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…21 Although BP nanosheets have also been extensively studied for their antibacterial effects, most studies have only utilized the CFU method to evaluate their antibacterial activity. 9, 10 In our previous studies, we noticed a significant discrepancy between the results obtained from the growth curve and CFU methods, 22,23 indicating that BP nanosheets may induce bacteria to enter the VBNC state. This speculation is supported by similar findings reported by Naskar et al 11 However, the underlying mechanisms of this response to BP nanosheets and the induction of the VBNC state by nanomaterials have not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 93%
“…The copyright holder for this preprint this version posted June 21, 2024. ; https://doi.org/10.1101/2024.06.17.599389 doi: bioRxiv preprint Previous studies assessing the bacterial toxicity of BP nanosheets have typically relied on methods such as growth curve analysis, the CFU method, and morphological observation. [9][10][11]22 However, these methods often fail to detect the presence of bacteria in the VBNC state, leading to an oversight of the VBNC state in bacteria exposed to BP nanosheets. In contrast, our findings clearly demonstrated that there were more VBNC cells than culturable cells when exposed to BP nanosheets (Figure 2g).…”
Section: Calculation Of the Percentage Of Vbnc Cellsmentioning
confidence: 99%
“…In addition, the expression of partial amino acid metabolic pathways involved in the TCA cycling was also upregulated, these include the arginine and proline metabolism pathway (responsible for intracellular αketoglutarate production) (Figure 4I and Table S4), the lysine degradation-associated genes (involved in acetyl-CoA synthesis) (Figure 4J), and the valine, leucine, and isoleucine metabolic pathways (involved in NADH production) (Table S5). 52,57 Notably, the expression of NADH dehydrogenase (nuoGHIJKLMN, critical for transferring electrons to coenzyme Q) increased by 53∼245% under DMP exposure, and the ATP synthase (atpABCDEFGH) showed 25∼66% upregulated expression (Figure 4F) to favor improved energy metabo- lism. 58 Overall, the above results show that diverse metabolic pathways, including the EMP, TCA cycle, oxidative phosphorylation, amino acid synthesis, and metabolism, were stimulated by DMP, resulting in improved ATP supply and higher bacterial motility to accelerate eARG transformation.…”
Section: Changes Of Bacterial Transformation Frequency Inmentioning
confidence: 99%
“…In fact, previous studies have indicated that Gram-positive bacteria are more susceptible to 2D nanomaterials than Gram-negative bacteria, possibly due to differences in bacterial membrane structure. [39][40][41][42][43] The outer membrane of Gram-negative E. coli provides protection against physical damage caused by the sharp edges of GNSs. 44 Despite the absence of outer membrane protection in Gram-positive S. aureus, their smaller spherical morphology allows utilization of GNSs as a shelter, reducing the exposure density of sharp edges to the membrane relative to rod-shaped cells.…”
Section: Mechanisms and Implicationsmentioning
confidence: 99%